2020
DOI: 10.1186/s13063-020-04562-1
|View full text |Cite
|
Sign up to set email alerts
|

Report of a Delphi exercise to inform the design of a research programme on screening for thoracic aortic disease

Abstract: Objectives: To inform the design of a clinical trial of a targeted screening programme for relatives of individuals affected by thoracic aortic disease, we performed a consensus exercise as to the acceptability of screening, the optimal sequence and choice of tests, long-term patient management, and choice of trial design. Methods: Working with the Aortic Dissection Awareness UK & Ireland patient association, we performed a Delphi exercise with clinical experts, patients, and carers, consisting of three rounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Uptake may be higher in the acute setting, as recommended by a recent Delphi exercise. 9 Second, in those probands who expressed an interest in the study, the uptake of cascade screening in their FDR and SDR was high, accounting for 54% of participants. This may reflect the desire of people at risk to know more about their likelihoods of developing the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uptake may be higher in the acute setting, as recommended by a recent Delphi exercise. 9 Second, in those probands who expressed an interest in the study, the uptake of cascade screening in their FDR and SDR was high, accounting for 54% of participants. This may reflect the desire of people at risk to know more about their likelihoods of developing the disease.…”
Section: Discussionmentioning
confidence: 99%
“…4 , 5 , 8 As a result, there is uncertainty around the screening of relatives with regard to screening modality, prognosis, and genetic counseling. 6 , 9 Therefore, the present study aimed to investigate the feasibility of a tailored imaging and genetic testing approach in relatives of probands affected by both sporadic and familial NS‐TAD.…”
mentioning
confidence: 99%
“…In addition to health outcomes and provider-centric outcomes, data are needed to characterize patient awareness regarding the genomic contribution to dissection, commitment to action, and adherence to management recommendations after genomic risk assessment and counseling. Research priorities outlined by this Working Group were consistent with themes reported by a patient-centered collaborative in the United Kingdom and Ireland, which included a need for early screening programs, healthcare provider engagement, and multidisciplinary care with psychological support and longitudinal follow-up [ 55 ]. Cost-effectiveness studies were not deemed high priority by patient stakeholders in either collaborative working group but were acknowledged as necessary measures of clinical utility by clinicians.…”
Section: Clinical Utility and Access To Genomic Medicine Servicesmentioning
confidence: 90%
“…Additionally, earlier critiques on the Delphi method itself include a potential pressure to conformity among the panel (Bolger & Wright, 2011; Woudenberg, 1991). Furthermore, the potential dilemma of an artificial consensus might occur, if a smaller subgroup of Delphi panelists makes disproportionately high numbers of revisions and thereby influences the discussion process and the result more strongly (Abbasciano et al, 2020; Birko et al, 2015). In the case of our research, we could not find any indication for the two validity threats.…”
Section: Implications Conclusion and Further Researchmentioning
confidence: 99%